Immaterial animals and financialized forests: Asset manager capitalism, ESG integration and the politics of livestock. (November 2022) - Brice, Jeremy; Cusworth, George; Lorimer, Jamie; Garnett, Tara
This article uses interviews with responsible investment professionals to examine the extent to which institutional equity investors, and specifically 'universal owners' with highly diversified shareholdings, engage with public issues associated with livestock agriculture. As share ownership becomes increasingly concentrated, and the market for Environmental, Social and Governance investment products grows, these investors are increasingly involved in governing the activities of publicly traded corporations (including leading agribusinesses). This paper brings together political economy and marketization studies research to explore how universal owners become concerned about particular environmental and ethical problems, why they overlook other public concerns, and in what ways their selective engagement with ethico-political issues might be altering the content of food politics. Comparing universal owners' engagements with farm animal welfare issues and with tropical deforestation within animal feed supply chains, we argue that these institutions engage with tropical deforestation because it presents a financially material risk to firms across multiple industries. By contrast, the specificity of farm animal welfare issues to agribusinesses means that they do not pose a material risk to the overall performance of universal owners' highly diversified asset portfolios. Efforts to concern universal owners about livestock agriculture's social, environmental and health impacts thus generate a food politics which focuses primarily on risks to global economic systems and renders animals themselves distinctly immaterial.